Penerapan Metode Kooperatif Tipe STAD dalam Meningkatkan Prestasi Belajar Pendidikan Pancasila dan Kewarganegaraan (PPKn) pada Siswa Kelas IX-1 SMPN 2 Keruak Masa Pandemi Covid 19 Semester I Tahun Pelajaran 2021-2022 - Ain, Hurul (MASALIQ, 2021)
In achieving the educational goals mandated by law, namely equipping students with logical, analytical, systematic, critical, and creative thinking. Therefore, teachers are required to be able to use learning models so that the material is easily understood or understood by students. The purpose of this classroom action research (CAR) is to determine the extent to which students' learning outcomes in Pancasila and Citizenship Education (PPKn) are improved by applying the Type Cooperative Method. STAD. In this classroom action research (CAR), it is carried out in 2 cycles, from the results of the actions taken it is proven to be able to improve student learning outcomes by achieving the classical mastery that is set at 85%. Classical completeness 71% obtained in the first cycle, can be increased in the second cycle to 93%. In terms of student activity, there was also an increase, namely in the first cycle, the moderately active category increased to an active category. The results of this action research indicate that the application of the STAD Type Cooperative Method can improve student learning outcomes in Pancasila and Citizenship Education (PPKn) lessons with completeness reaching 93%.